Pervasiveness of Tobacco associated Oral Lesions among Women residing in Urban Slum of Bhopal - Upadhyaya, Shubhangi; Saxena, Vrinda; Jain, Manish; Tiwari, Vidhatri; Tomar, Nilesh; Pathak, Anuja (Journal of Orofacial Research, 2015)
Background: The urban-slum population has emerged as a new section which is known to fare very poorly on issues related to oral health. The proportion of the urban-slum population is also increasing at a rapid rate. The deleterious habits are highly prevalent so is the tobacco, in this population. Hence, the study was steered to evaluate the association of tobacco consumption and oral mucosal lesion (OML) in this population. Aim of the study: To assess the prevalence and patterns of tobacco use and related oral lesions among women residing in urban-slum of Bhopal city (Central India). Materials and methods: The descriptive cross-sectional questionnaire based study was deliberated by a convenience sample technique. A predesigned structured questionnaire was the tool used for data collection. All the female participants available on the day of survey were included. Entailing in the study was 130 participants residing in various slums of Bhopal city. Results: Oral health is an important parameter to extent holistic health. The quantum of tobacco is widely prevalent among under-privileged populations. Ramifications are depleted oral health and gross impact on overall health too. Tobacco affects from mild to major lesions in oral cavity. Most devastating is oral cancer directly related to tobacco consumption. Conclusion: The concludory points derived out of this study are sufficient enough to conclude that women were aware of the trivial general ill effects of tobacco consumption but major harmful effects on oral health is still below the iceberg due tounawareness and low socioeconomic status (SES).